Use of high-resolution thermogravimetric analysis (HRTG) technique in spent FCC catalyst/Portland cement pastes - Soriano, L.; Tashima, M. M. [UNESP]; Bonilla, M.; Paya, J.; Monzo, J.; Borrachero, M. V. (Springer, 2015)
Thermogravimetric analysis is one of the most common instrumental techniques used for the characterization of pastes, mortars and concretes based on both calcium hydroxide and Portland cement. Important information about pozzolanic materials can be assessed concerning calcium hydroxide consumption and the formation of new hydrated products. Nevertheless, in some cases, problems associated with the overlapped decomposition processes for hydrates make the analysis of obtained data difficult. In this paper, the use of high-resolution thermogravimetric analysis, a powerful technique that allows separating decomposition processes in analysis of hydrated binders, was performed for spent FCC catalyst-Portland cement pastes. These pastes were monitored for 1, 4, 8 h and 1, 2, 3, 7 and 28 curing days. In order to study the influence of the pozzolanic material (spent FCC catalyst), Portland cement replacements of 5, 15 and 30 % by mass were carried out. The presence of spent FCC catalyst in blended pastes modified the amount and the nature of the formed hydrates, mainly ettringite and stratlingite.
Keywords: High-resolution thermogravimetric analysis; Portland cement; Spent FCC; Pozzolan